Analisis Inovatif Peraturan Daerah terkait Pengelolaan Zakat dalam Perspektif Prinsip-prinsip Pemerintahan yang Baik - Nuvazria Achir; Mohamad Hidayat Muhtar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2023)
The emergence of various regional legislative products concerning zakat management, such as the Regional Regulation of Pohuwato Regency Number 6 of 2015 on Zakat Management, harbors potential complications. These issues pertain mainly to the implementation of good governance principles and innovation in the regulations and practices of zakat management. The primary aim of this study is to evaluate the effectiveness and accountability of zakat management in Pohuwato Regency, as enforced through the Regional Regulation of Pohuwato Regency Number 6 of 2015 on Zakat Management. Furthermore, this study seeks to identify critical steps that ought to be considered when addressing the challenges of zakat management. The adopted research methodology is empirical legal research, with an analytical and observational approach. The focus of this research is to gather factual data through case studies and interviews, as well as observing and analyzing the practical application and enforcement of the law. The study's findings highlight that coordination, transparency, accountability, empowerment of mustahiq (the poor and needy), and zakat literacy should be considered to establish effective and efficient zakat management in Pohuwato Regency. Vital steps requiring attention include professionalism, accountability, transparency, public participation, effectiveness, and coordination between agencies. By implementing these steps, zakat can optimize its benefits, thereby enhancing the quality of life and overall welfare of the people.